Corruption and Social Interaction: Evidence from China - Bin Dong; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2010)
We explore theoretically and empirically whether social interaction, including local and global interaction, influences the incidence of corruption. We first present an interaction-based model on corruption that predicts that the level of corruption is positively associated with social interaction. Then we empirically verify the theoretical prediction using within-country evidence at the province-level in China during 1998 to 2007. Panel data evidence clearly indicates that social interaction has a statistically significantly positive effect on the corruption rate in China. Our findings, therefore, underscore the relevance of social interaction in understanding corruption.
Keywords: K42; D72; D64; O17; J24; 330; Awards; Signals; Status; Anonymity; Globalization